Prevalence and influencing factors of hyperuricemia among hypertensive patients registered at community health service centers in suburb of Shanghai: a cross-sectional survey - Fei WU; Mei YANG; Qinghua YAN; Zhaoyu CHANG; Qiuyan CHEN; Yuheng WANG; Qinping YANG; Minna CHENG; Jianrong XU; Yang MENG; Yan SHI (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the prevalence and determinants of hyperuricemia (HUA) among hypertensive patients registered at community health service centers in suburb of Shanghai for promoting prevention and management of HUA in primary health institutions. MethodsThe participants of the study were 3 600 hypertensive patients randomly recruited from chronic disease patients registered at two community health service centers in a suburban district of Shanghai city. Face-to-face interview with a self-designed questionnaire and the International Physical Activity Questionnaire, physical examination, laboratory tests were conducted among the participants during October − December 2021. The prevalence of HUA was described and unconditional multivariate logistic regression analysis was used to analyze determinants of HUA. ResultsAmong the 2 899 eligible participants, 882 were identified as having HUA, with an overall prevalence of 30.42% and not significantly different gender-specific prevalence of 31.96% for the males and 29.15% for the females (P > 0.05). The results of unconditional multivariate logistic regression analysis indicated that hyperlipidemia, chronic kidney disease, overweight, and obesity were risk factors for HUA but suffering from diabetes, medication with angiotensin receptor blockers (ARBs) or with calcium channel blockers (CCBs) were protective factors against HUA for all the participants; while for the male participants, hyperlipidemia, chronic kidney disease, overweight, obesity were risk factors and suffering from diabetes was a protective factor; for the female participants, aged 80 years and above, hyperlipidemia, chronic kidney disease, overweight, obesity were risk factors but medication with ARBs or with CCBs were protective factors. ConclusionThe prevalence of HUA was relatively high in hypertensive patients at community health service centers in suburb of Shanghai. The result suggests that uric acid should be monitored among the hypertensive patients with chronic kidney disease, hyperlipidemia, overweight or obesity and antihypertensive drugs should be selected carefully for hypertensive patients complicated with HUA.